Selibat atau Menikah?: Petunjuk-Petunjuk Menentukan Pilihan Berdasarkan Studi Eksposisional 1 Korintus 7 - Natallina, Elisabeth (Veritas : Jurnal Teologi dan Pelayanan, 2019)
Celibacy or Marriage ?: Instructions for Making Decision Based on Expositional Study of 1 Corinthians 7. The inner struggle to decide whether to marry or be celibate is a struggle for some Christians, especially young people. Choosing one of these two options can be difficult with some complexity due to a lack of understanding of the Bibleâ€™s principles related to this issue. Some believers do not understand the biblical instructions that can help them in their struggle to be married or celibate. While this struggle continues, data shows that the quantity level of singleness is increasing globally in the world and in Indonesia itself. Whether to be married or celibate, the decision to determine between these two options, according to Paul, must be based on their gift.Â  This paper will explain the instructions that can be learned from Paul's advice in 1 Corinthians 7 to make decisions about the status of life, especially celibacy.